Big data analytics tools and technology for effective planning - Somani, Arun K.; Deka, Ganesh Chandra (Chapman & Hall/CRC Big Data Series, 2018)
The proposed book will discuss various aspects of big data Analytics. It will deliberate upon the tools, technology, applications, use cases and research directions in the field. Chapters would be contributed by researchers, scientist and practitioners from various reputed universities and organizations for the benefit of readers.